f(-5)=-3x+4

Simple and best practice solution for f(-5)=-3x+4 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for f(-5)=-3x+4 equation:


Simplifying
f(-5) = -3x + 4

Reorder the terms for easier multiplication:
-5f = -3x + 4

Reorder the terms:
-5f = 4 + -3x

Solving
-5f = 4 + -3x

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Divide each side by '-5'.
f = -0.8 + 0.6x

Simplifying
f = -0.8 + 0.6x

See similar equations:

| 3/p-5=-14 | | 5(13+k)= | | (10a+4)= | | 2x+3x*y=3 | | 5.54x+100=30.6916+10x | | 4x1/1.2 | | 3x-5+4x=-40 | | f(-5)=3x+4 | | (10a-4)= | | 6r+r=6r-5 | | 17x=1.3 | | 10/11x-9/11=4 | | 33-12x+25x=-6 | | 72+3x=7x-10 | | 7(r-9)=35 | | 1/2x^5=512 | | 72=4x-10 | | 2(2x+6)+8-3=14+11+15 | | Y-2=9(9x+6) | | b+10=6b | | 1/2×=13 | | 5x+10-15x=30 | | 9999999999999999999999999999999999999999999999999999999999999999999999999999999= | | y=4x^(2/3) | | 4(j+6)=72 | | 5x-10=440 | | -7x+6-9x=6 | | 3(5.45)-7y=3 | | 10c-14=86 | | 14y=-14x-56 | | 49+x=x^2+2x+1 | | 6p+8=62 |

Equations solver categories